PHÂN TÍCH TRÌNH TỰ GIEN PHES CHO VIỆC XÁC ĐỊNH LOÀI VI KHUẨN LACTIC SINH BACTERIOCIN - Đoàn, Nguyễn Thị Lâm; Mạnh, Ngô Xuân; Đà, Nguyễn Thị; Hằng, Vũ Thị; Bắc, Nguyễn Xuân (Vietnam Journal of Science and Technology, 2012)
PHES GENE SEQUENCE ANALYSIS FOR THE IDENTIFICATION OF A LACTIC ACID BACTERIUM PRODUCING BACTERIOCIN FROM NEM CHUA The aim of this study was to identify species level of producing bacteriocin strain isolated from Ha Noi nem chua (DV4.10) by pheS gene sequencing analysis. Genomic DNA DV4.10 was extracted. Then pheS gene was run the first PCR with PheS-21-F(5′-CAYCCNGCHCGYGAYATGC-3′) and PheS-22-R (5′-CCWARVCCRAARGCAAARCC-3′). PCR product was checked by by electrophoresis on a 1% (wt/vol) agarose gel at 75 V for 45 min with marker (SmartLadder, Eurogentec, Searing, Belgium). PCR product of DV4.10 collected a bold band at 450 bp position similar to size of pheS gene [6]. This PCR product continued to run the second PCR with seperated primer, purified, sequenced and comparated to sequencing of known sequence database in EMBL or BCCM/LMG collection of Gent university, Belgium. The result showed that DV4.10 is Lactococcus lactis subsp. lactis species. Thus, the pheS gene sequence provides a useful tool. It have a higher discriminatory power for reliable identification of species level.